First clinical trials of novel ENaC targeting therapy, SPX-101, in healthy volunteers and adults with cystic fibrosis. (October 2019) - Couroux, Peter; Farias, Paulina; Rizvi, Leena; Griffin, Katherine; Hudson, Christie; Crowder, Timothy; Tarran, Robert; Tullis, Elizabeth
Abstract: Background: ENaC inhibition has been investigated as a CF treatment; however, small molecule inhibitors of ENaC lack efficacy and/or have shown dose-limiting hyperkalemia. SPX-101 is a novel, investigational small peptide (SPLUNC1 mimetic) that regulates ENaC density with the potential for efficacy without systemic effects. Methods: Two trials are presented: The first was a Phase 1, 2-part, randomized, double-blind, placebo-controlled, ascending-dose study of nebulized SPX-101 in healthy adults. Part 1 evaluated 4 single doses of SPX-101 ranging from 20 to 240 mg. Part 2 evaluated a 14-day regimen of SPX-101 at 4 doses of SPX-101 ranging from 10 to 120 mg BID. Pharmacokinetics, adverse events, spirometry, vital signs, electrocardiograms, pulse oximetry, and clinical laboratory values were assessed. The second trial was a tolerability-confirming, Phase 1b, open-label study conducted in 5 adult subjects with CF. Ascending doses of SPX-101 inhalation solution (10 mg–120 mg BID) were administered for 7 days. Safety was assessed as described above. Results: All 64 healthy volunteers (32 in each Part) completed the single and multiple dose study. SPX-101 was well tolerated with little/no systemic exposure and with no hyperkalemia. Adverse events were generally mild with reported respiratory events associated with the purported pharmacological activity of SPX-101. Tolerability of SPX-101 was similarly observed in adults with CF; all 5 subjects treated with SPX-101 completed the study. Conclusions: SPX-101 was well-tolerated across a range of doses and had little/no systemic exposure in healthy adults and adults with CF, thus supporting further study in patients with CF. Clinicaltrial.gov registration: NCT03056989. Highlights: First-in-human studies of novel SPX-101 therapy for the treatment of CF are summarized. Internalization of ENaC via SPX-101 is safe, well tolerated and does not cause hyperkalemia. These results support further evaluation of SPX-101 in treating patients with cystic fibrosis.